Description of Student Attitudes in Physics Subjects Towards Reading Interest - Dinda Febrina Alvita; Blessing Ifeoma Odum; Kullawat Inthaud (Schrödinger: Journal of Physics Education, 2023)
Purpose of the study: This study aims to determine the attitudes of class XI students of Public senior high school 3 Muaro Jambi and Senior Secondary School Anagada towards reading interest. Methodology: This research is quantitative research. The population in this study were class XI students of Public senior high school 3 Muaro Jambi and Senior High School Anagada. The sampling technique used simple random sampling so that 60 students were obtained. The data collection technique in this research is by distributing reading interest and attitude questionnaires to students via Google Form which contains positive and negative statements for each student. Data analysis uses descriptive statistics. Main Findings: The results of the research show that the attitudes of high school students towards learning physics tend to be in the good category. Then it was discovered that high school students' reading interest in physics learning tended to be in the good and very good categories. These findings can be the basis for further research to further explore the factors that influence students' reading preferences. It is hoped that further research can provide a deeper understanding of the dynamics of high school students' interest in reading. Novelty/Originality of this study: This research was conducted using a quantitative descriptive method that describes students' learning attitudes and reading interest in high school physics subjects. This can provide valuable insight into curriculum development, teaching methods, and efforts to increase students' interest and understanding of physics reading material.